Pengaruh Prinsip Technology Acceptance Model (TAM) Terhadap Kepuasan Pelanggan Aplikasi Ojek Online Xyz - Subowo, S.Kom., M.T.I., Moh Hadi (Universitas Islam Negeri Walisongo Semarang, 2020)
The use of the online taxibike XYZ application is based on the Technology Acceptance Model (TAM) theory. The online taxibike XYZ application can be good if it has a good assessment based on the TAM variable. The purpose of this study is to obtain empirical evidence regarding the effect of the TAM principle on customer satisfaction. This study uses a quantitative causal research method to analyze the application of the Technology Acceptance Model (TAM) principle to online taxibike XYZ application customer satisfaction. The instrument in this study used a questionnaire instrument with a closed questionnaire type. The data analysis technique used three tests: data quality test, hypothesis test, and classical assumption test. All variables x, both reliability, flexibility, privacy, accessibility, ease to use, all positively influence customer satisfaction